Analysis of Student Errors in Algebra Material Using a Modern Diagnostic Approach - Titiani Reza Rahamdani; Elma Maula Safitri (Gema Cendekia Institute, 2025)
This study aims to analyze students' errors in solving algebra problems using a modern diagnostic approach based on error analysis. This approach allows for systematic identification of error patterns through classification into conceptual, procedural, and strategic aspects. The research method used was descriptive qualitative with 30 eighth-grade students in a public junior high school as subjects. Data were collected through diagnostic tests and task-based interviews. The results showed that conceptual errors were the most dominant type of error (45%), followed by procedural errors (35%), and strategic errors (20%). These findings revealed that most students did not understand the meaning of variables, the principles of algebraic operations, and the process of simplifying algebraic forms. This study recommends the development of visual reasoning-based instruction, scaffolding, and the use of digital diagnostic technology to improve students' understanding of algebra.